The despair of disparity: the connecttion between foreign language anxiety and the recognition of proficiency differences in L2 skills - Gregersen, Tammy (Lenguas Modernas, 2017)
This study examines the relationship between foreign language (FL) anxiety and learners’ recognition of their proficiency differences across the four skills: reading, writing, speaking, and listening. To this end, 191 French and Spanish FL graduate and undergraduate students were surveyed to assess their FL anxiety attributable to self-perceived L2 skill disparity, and their personal assessment of the importance of each skill. Results suggest that a FL leamer’s awareness of skills disparity, coupled with a high value placed on the lacking skills, elicited heightened FL anxiety when leamers engaged in activities using the deficient skill(s). These flndings suggest a need to consider integrated approaches to language instruction that foster mutually supportive growth of the four skills simultaneously.